Histologi Tubulus Seminiferus dan Kadar Testosteron Tikus yang Diberi Pakan Imbuhan Tepung Daun Kaliandra dan Kulit Nanas (HISTOLOGY OF SEMINIFEROUS TUBULES AND TESTOSTERONE LEVEL OF RAT GIVEN CALLIANDRA LEAF MEAL AND PINEAPPLE PEELS IN THE DIETS) - Setyawati, Iriani; Putra, I Gusti Ngurah Agung Dewantara; Roni, Ni Gusti Ketut (Jurnal Veteriner; Vol 18 No 3 (2017), 2017)
Calliandra calothyrsus leaf contains 17-28% protein which is hihly potential for use as source of protein supplement for animal feed. However, the plants also contain high level (>10%) of condensed tannins as antinutritional effects which may reduce consumtion efficiency of diet. The addition of protease (bromelain) into feed containing tannin is expected to decrease the negative effects of tannins. Bromelain can be obtained from the pineapple plant ( Ananas comosus ) including on the peels. This study was conducted to determine the effect of calliandra tannin combined with bromelain protease of pineapple peels in the feed on testicular histology and testosterone level of rats feeded during the growth period. The feeding experiment on post-weaning male rats was conducted using a completely randomized factorial design (4 main factors x 4 subfactors). The main factors were calliandra leaf meal substitution of 0; 10; 17.5 and 25% in the diets and subfactors were addition of pineapple peels, 0; 4.35; 8.70 and 13.05 g/rat/day. Rats were divided into 16 groups and were feeded the diets for two months (during the growth period). The results showed the susbtituion of feed with calliandra leaf had no sigbnificant effecton the thickness of the seminiferous tubules, but it appeared to have significant effect on the histology of seminiferous tubules. Increased pineapple peels level in the diets containing calliandra decreased wall thickness of the seminiferous tubules of the rat testes, indicating that bromalein fastened the maturation of spermatozoa. The addition of pineapple peels into the diet containing calliandra had a significant interaction effect on testoteron levels of male rats, but the testoteron levels among all treated rats were still within the normal range. ABSTRAK Daun kaliandra (Calliandra calothyrsus) mengandung protein 17-28% sehingga potensial sebagai sumber protein pakan ternak, namun tanaman ini mengandung condensed tannin cukup tinggi (>10%) yang bersifat antinutrisi. Penambahan enzim protease (bromelin) pada pakan yang mengandung tanin diharapkan dapat mengatasi dampak negatif tanin. Bromelin dapat diperoleh dari tanaman nanas ( Ananas comosus ) termasuk dari kulit buahnya. Penelitian ini bertujuan untuk mengetahui pengaruh tanin daun kaliandra dalam pakan yang dikombinasikan dengan protease bromelin dari limbah kulit nanas terhadap histologi testis dan kadar hormon testosteron tikus jika diberikan pada masa pertumbuhan. Penelitian ini merupakan percobaan pakan pada tikus jantan pascasapih selama masa pertumbuhan dengan Rancangan Acak Lengkap pola faktorial berjenjang 4x4 dengan level substitusi tepung daun kaliandra 0; 10; 17,5 dan 25% dalam ransum ( main factor ) dan dosis aditif kulit nanas 0; 4,35; 8,70 dan 13,05 g/ekor/hari ( sub factor ). Tikus dibagi menjadi 16 unit percobaan dan diberi perlakuan ransum selama dua bulan (masa pertumbuhan). Hasil penelitian menunjukkan bahwa tebal dinding tubulus seminiferus testis tikus tidak berbeda nyata, namun tampak adanya perbedaan pada gambaran histologi yang meliputi struktur membran basal, susunan antar sel-sel spermatogenik pada dinding tubulus, serta gambaran sel-sel spermatozoa di dalam lumen tubulus. Peningkatan dosis kulit nanas dalam ransum yang mengandung kaliandra menurunkan tebal dinding tubulus seminiferus. Aditif kulit nanas ke dalam ransum yang mengandung kaliandra menunjukkan interaksi yang memengaruhi kadar hormon reproduksi dengan menurunkan kadar hormon testosteron tikus jantan walaupun masih dalam kisaran normal.